New insights into the heat capacity enhancement of nano-SiO2 doped alkali metal chloride molten salt for thermal energy storage: A molecular dynamics study. (July 2023) - Yang, Xueming; Ji, Chang; Liu, Jieting; Ma, YongFu; Cao, Bingyang
Abstract: Molten salts and their based nanofluids are important media for heat transfer and thermal energy storage in concentrated solar power (CSP) system. To improve the overall efficiency of the CSP plants, it is important to increase the specific heat capacity of molten salt to the extent possible. Nanomaterials have been doped in molten salt to enhance the specific heat capacity of molten salt; however, the mechanism of enhancement in specific heat capacity caused by doping of nanoparticles in molten salt is still unclear. In this work, the Buckingham force field parameters for alkali metal chloride molten salts (KCl, NaCl, LiCl) were first derived and carefully validated. The specific heat capacities, viscosities, and self-diffusion coefficients of pure molten salts and the specific heat capacities of molten-salt-based nanofluids with SiO2 nanoparticles were investigated by molecular dynamics (MD) simulations. The calculated thermophysical properties of the chloride molten salts using the derived Buckingham potential parameters are in good agreement with the experimental data, and the overall prediction performance is better than that of the BMH potential. Results show that the specific heat capacity of molten salt first increases and then decreases with increasing SiO2 doping ratio, reaching a maximum value at 1 wt%. The specific heat capacities of KCl, NaCl and LiCl nanofluids with 1 wt% SiO2 nanoparticle are increased by 6.2 %, 8.6 % and 19.8 % compared to the base salts, respectively. Number density, radial distribution function, coordination number curves, and energy of the nanofluid system were systematically analyzed. It is found that the increase of the specific heat capacities of the molten salt-based nanofluids can be explained by the energy and coordination number change caused by the number density mismatch of cations and anions. Interestingly, the local delamination of cations around SiO2 nanoparticle surfaces in LiCl-SiO2 nanofluids is clearly observed and visualized for the first time; it is a phenomenon well explained by the analysis of number density and contributes to the further enhancement of the heat capacity. The findings of this work could provide important fundamentals in understanding and designing more efficient molten salt nanocomposites for thermal energy storage in future studies. Highlights: New insights on heat capacity enhancement of nano-SiO2 doped alkali metal chloride molten salt are proposed. The heat capacity enhancement can be explained by the local delamination and number density mismatch of cations and anions. Buckingham force field parameters for alkali metal chloride molten salts were first derived and carefully validated. Number density, coordination number curves, and energy of the nanofluid system were systematically analyzed.